Metodologias para avaliação da qualidade fisiológica e identificação do ponto de colheita de sementes de cultivares crioulas de milho - Noal, Gisele (2013)
Cultivars of maize landraces provide the farmer seed production with high genetic variability, resistance and wide adaptation, beyond the advantage that the farmer can select them and store them for use next season, without the purchase of inputs. However, due to the high genetic variability, standardized tests to determine the physiological quality of the seeds need to be adapted so that they can be applied to the Land varieties. Therefore, this study aims at evaluating different methodologies for evaluation of physiological and sanitary quality for growing maize landraces. We used seeds produced by farmers Seed Guardians of Creole Ibarama - RS. We evaluated the effect of these seeds (using various tests) and sanitary quality (for both methods of detection). Moreover, there was monitoring the process of seed maturation in different harvest periods. The germination test showed variations between the evaluation periods and different temperatures tested, and that the temperature of 25 º C and 6 º day of evaluation, we obtained the highest percentage of germination, for most cultivars. In cold test response variability occurred when the cultivars analyzed at different temperatures and exposure times. The pH of the exudate tests showed no significant difference between the variations tested methodologies. Land varieties for the tetrazolium test can be performed with less concentration of tetrazolium salt (0.07%). The point of harvest, as the physiological quality showed better results in the period was 20 to 30% moisture (held last harvest) and fungal incidence ranged between periods of maturation evaluated.